PENGARUH BUDAYA KOMPETITIF DAN BUDAYA DISIPLIN TERHADAP PRESTASI SANTRI MA’HAD AL QOSIMY MADRASAH ALIYAH NEGERI 2 BANYUWANGI - Hidayati, Nur; Nafia, Ilma (Jurnal Manajemen Pendidikan Islam Darussalam, 2024)
The objectives of this research are 1). To find out whether there is an influence of competitive culture on the achievement of Santri Ma'had Al Qosimy MAN 2 Banyuwangi. 2). To find out whether there is an influence of discipline culture on the achievement of Santri Ma'had Al Qosimy MAN 2 Banyuwangi. 3). To determine the influence of Competitive Culture and Disciplinary Culture together on the Achievement of Santri Ma'had Al Qosimy MAN 2 Banyuwangi. This research uses quantitative descriptive methods. The number of samples in this study was 109 respondents. The respondents in this research were all female students of Ma'had Al Qosimy MAN 2 Banyuwangi. Determination of the sample using non-probability sampling techniques or saturated samples. Data collection techniques include giving questionnaires to respondents, observation and documentation. In proving and analyzing this, validity and reliability tests, normality tests, multiple linear regression tests and t tests (partial) and F tests (simultaneous) are used. The test results show that: 1) partially influences the achievement of the students of Ma'had Al Qosimy MAN 2 Banyuwangi. Partial test results show that Competitive Culture (X1) has a regression coefficient of 5.291 > 1.980, so H0 is rejected and Ha is accepted. Disciplinary Culture (X2) has a regression coefficient of 2.838 > 1.980, so H0 is rejected and Ha is accepted. Both variables have a significance value of <0.05. Thus the results of the t test (partial) show that there is a positive and significant influence of competitive culture (X1) and disciplinary culture (X2) on the achievement of students (Y) Ma'had Al Qosimy MAN 2 Banyuwangi.